Menyuarakan Jati Diri Anak Bangsa di Nagari Guguak Malalo - Nasution, Nadia Putri; Latifah Mihar; Nanda Channisa Putri; Sri Febriani; Gilang Efendi Ramadhan; Esy Maestro (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The Community Service Program (KKN) in Nagari Guguak Malalo aims to examine the role of traditional dance in cultural preservation and the formation of national identity among young people. The implementation method includes participatory observation, dance training, and organizing art performances with local studios. The results show that traditional dance is an effective medium for instilling cultural values, increasing self-confidence, and shaping the identity of the younger generation. The art performance successfully showcased various traditional dances such as Tari Piring and Tari Indang with high enthusiasm from participants. The conclusion is that traditional dance has a vital role in cultural preservation and character building of the nation's children, requiring continuous support from various parties to ensure its sustainability.